11.2k views
1 vote
Use back-substitution to solve the system of linear equations.

Use back-substitution to solve the system of linear equations.-example-1
User Ittupelo
by
4.8k points

1 Answer

3 votes

Answer:

x = 38

y =2

z=-1

Explanation:

z = -1

Substituting into the second equation

y-z =3

y - -1 =3

y+1 = 3

Subtract 1

y+1-1= 3-1

y =2

Substituting into the first equation

x -2y +2z = 32

x -2(2) +2(-1) = 32

x-4-2 = 32

x-6 = 32

Add 6 to each side

x-6+6 =32+6

x = 38

User Enigmadan
by
4.6k points